Ultrasound-Guide Hydrodissection for Ulnar Nerve Entrapment at Arcade of Struthers - Kamala Kan Nur Azza; Said Sofwan; Albertus Sugeng Wibisono (Faculty of Medicine, Brawijaya University, 2022)
Background: Ulnar nerve entrapment (UNE) causes a tingling or numbness in the fourth and fifth fingers and appears when provoked by bending the elbow. In some severe cases, UNE often causes weakness of the fourth and fifth fingers when grasping or difficulty in coordinating movements. In severe cases, it causes muscle atrophy. Case: A 39-year-old male patient had complaints of pain and numbness in the right arm above the elbow radiating to the fourth and fifth fingers. There is a burning sensation on the right arm when exposed to the wind, with a visual analog scale (VAS) 4-5. Two years ago, the patient had a history of pain in his entire right arm and shoulder blade after falling from a cliff. The patient received treatment with mefenamic acid 500 mg, three times a day, ranitidine 150 mg, two times a day, but the pain did not improve. The patient was diagnosed with ulnar nerve entrapment at the arcade of Struthers. The patient was treated with hydrodissection using ultrasound guidance with 2% lidocaine and steroids (Triamcinolone Acetonide 40 mg/ml). Evaluation on the seven days after hydrodissection, burning sensation at the injection site, tingling and numbness have disappeared. Conclusion: Ultrasound-guided hydrodissection is clinically effective in ulnar nerve entrapment at the arcade of Struthers management.